2019
DOI: 10.1007/s00228-019-02674-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity risk factors and acetaminophen dose adjustment, do prescribers give this issue adequate consideration? A French university hospital study

Abstract: Hepatotoxicity risk factors and acetaminophen dose adjustment, do prescribers give this issue adequate consideration? a French university hospital study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…17 A French study reported that 50% (302/ 606) patients aged >75 years with 1 or more additional risk factor for toxicity (including low body weight or malnutrition) did not have their paracetamol dose reduced. 25 A recent study at a Swiss hospital reported that 1/3 (68/206) of patients aged >75 years with body weight <50 kg received >60 mg/kg/d. 26 In our study, in a majority (58.0%) of instances, the higher than recommended dose was initiated in hospital (either newly commenced in hospital or dose-increased after admission).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A French study reported that 50% (302/ 606) patients aged >75 years with 1 or more additional risk factor for toxicity (including low body weight or malnutrition) did not have their paracetamol dose reduced. 25 A recent study at a Swiss hospital reported that 1/3 (68/206) of patients aged >75 years with body weight <50 kg received >60 mg/kg/d. 26 In our study, in a majority (58.0%) of instances, the higher than recommended dose was initiated in hospital (either newly commenced in hospital or dose-increased after admission).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in New South Wales, Australia, where there was a reduced‐dose policy for paracetamol dosing in older patients, found that 28% (196/274) patients aged ≥65 years received >3 g/d of paracetamol, but patients' frailty status and body weight was not reported 17 . A French study reported that 50% (302/606) patients aged >75 years with 1 or more additional risk factor for toxicity (including low body weight or malnutrition) did not have their paracetamol dose reduced 25 . A recent study at a Swiss hospital reported that 1/3 (68/206) of patients aged >75 years with body weight <50 kg received >60 mg/kg/d 26 …”
Section: Discussionmentioning
confidence: 99%
“…2,17,18 In a French study, 50% of patients aged >75 years with risk factor for toxicity (low body weight or malnutrition) had their paracetamol dose not reduced. 17 In a recent Swiss study, the maximal daily dose of 60 mg/kg was exceeded in 30.1% of patients weighing <50 kg, as well as in 42.3% of patients weighing <60 kg. 18 In our hospital, paracetamol was the first drug taken in units.…”
Section: Resultsmentioning
confidence: 99%
“…As paracetamol is not associated with significant adverse effects than traditional nonsteroidal anti‐inflammatory drugs, paracetamol is recommended as first‐line therapy for the management of pain in older adults. Likewise, some studies reported paracetamol regimens in older adults that involved administrations >3 or 4 g/d 2,17,18 . In a French study, 50% of patients aged >75 years with risk factor for toxicity (low body weight or malnutrition) had their paracetamol dose not reduced 17 .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Quanto a generalização dos resultados, é possível iniciar uma discussão de implementação de medidas regulatórias para a retirada desses medicamentos do acesso livre dos consumidores, como por exemplo, remoção das prateleiras próximas ao caixa, redução da quantidade por embalagens ou blisters, colocação de alertas sobre dano hepático no rótulo e de dose máxima em texto nas embalagens do medicamento, tendem a reduzir o número de intoxicações e lesões associadas. 3,[26][27][28] Nos EUA, metade dos casos de insuficiência hepática aguda associam-se ao uso do paracetamol. 22 intoxicações por paracetamol associados a outros medicamentos, oito apresentam interações medicamentosa grave.…”
Section: Discussionunclassified